2019
DOI: 10.2147/cmar.s229585
|View full text |Cite|
|
Sign up to set email alerts
|

<p>Risk Assessment for Breast Cancer Development and Its Clinical Impact on Screening Performance in Iranian Women</p>

Abstract: IntroductionThe aim of this study is to estimate the objective and subjective risk and to examine their associations with three forms of breast cancer screening.MethodsThis cross-sectional study was conducted with a sample of 800 women aged 35–85 years from the community setting and outpatient clinic in Babol, the north of Iran. The demographic, socio-economic characteristics and the risk factor profiles were collected through in-person interview. The health belief model (HBM) and visual analog scales were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Results of three studies showed 52.9%, 30.9%, and 60% of females, did not know how to perform BSE or didn't have the necessary skills to do it (9)(10)(11). The mean of 5-year and lifetime BC risk perception was calculated 0.89 ±0.89 and 8.87 ±3.84, respectively (18). It was demonstrated that a higher 5-year risk perception had more predictive power for performing Mammo, while it did not predict achieving BSE or CBE.…”
Section: Resultsmentioning
confidence: 95%
“…Results of three studies showed 52.9%, 30.9%, and 60% of females, did not know how to perform BSE or didn't have the necessary skills to do it (9)(10)(11). The mean of 5-year and lifetime BC risk perception was calculated 0.89 ±0.89 and 8.87 ±3.84, respectively (18). It was demonstrated that a higher 5-year risk perception had more predictive power for performing Mammo, while it did not predict achieving BSE or CBE.…”
Section: Resultsmentioning
confidence: 95%
“…This model was automated with an interactive online program based on clinical and reproductive data of individuals' risk pro les that computes the actual 5-year and lifetime risk and also the average risk with similar age of individuals in the population of women. The details of this risk calculation were explained elsewhere 12 .…”
Section: Data and Instrumentsmentioning
confidence: 99%
“…The increasing incidence in developing counties is mainly attributed to changes in lifestyles and reproductive behaviors [6][7][8][9][10] . Because of the low performances of Iranian women in screening, the majority of patients are diagnosed at a higher stage of the disease that is corresponded with a high mortality rate [11][12][13] . To establish a preventive strategy for early detection, the risk assessment is primarily interested in BC from a public health perspective.…”
Section: Introductionmentioning
confidence: 99%
“…A cluster sampling technique was used to recruit individuals in the study in the randomly selected community-based clusters and also the outpatient clinic. The details of sampling methods were described elsewhere 12 . In brief, 20 randomly selected community-based clusters and 3 outpatient clinics in the major educational hospitals were used to select samples.…”
Section: Study Design and Subjectsmentioning
confidence: 99%
“…The increasing incidence in developing counties mainly attributed to changes in lifestyles and reproductive behaviors [6][7][8][9][10] . The majority of women with BC are diagnosed at a higher stage of the disease that is corresponded with a high mortality rate [11][12][13] . To establish a preventive strategy for early detection, the risk assessment is primarily interested in BC from a public health perspective.…”
Section: Introductionmentioning
confidence: 99%